2020
DOI: 10.46542/pe.2020.201.236248
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of depression, anxiety and stress among undergraduate pharmacy students in Nigeria

Abstract: Background: Mental health disorders are increasingly becoming a global concern among university students. The prevalence of depression, anxiety and stress among pharmacy students in Nigeria is unknown. Objective: This study sought to examine the occurrence of depression, anxiety and stress and associated sociodemographic factors among undergraduate pharmacy students in Nigeria. Methods: The study was an online-based cross-sectional descriptive survey conducted among students from seven pharmacy schools in Nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 81 publications
2
18
0
Order By: Relevance
“…Respondents in this study were evenly spread across gender. This has been the finding of another study conducted among pharmacy students in Nigeria (Aluh, Abba, & Afosi, 2020). The majority of the respondents in this study were within the 18-25 age category.…”
Section: Discussionsupporting
confidence: 82%
“…Respondents in this study were evenly spread across gender. This has been the finding of another study conducted among pharmacy students in Nigeria (Aluh, Abba, & Afosi, 2020). The majority of the respondents in this study were within the 18-25 age category.…”
Section: Discussionsupporting
confidence: 82%
“…Also, we found that being an undergraduate was significantly associated with more worries about achieving academic milestones compared to being in postgraduate studies. Other studies have reported decreased distress among university and college students in higher academic levels (Aluh, Abba, & Afosi, 2020;Njim et al, 2020;Votta & Benau, 2014), while some did not find any difference (Emmanuel, 2016;Opoku-Acheampong et al, 2017). A possible reason for decreased worries about achieving academic milestones among postgraduate students could be that they are able to make higher wages having had a degree.…”
Section: Discussionmentioning
confidence: 94%
“…A study conducted by Lamidi et al (10) on depression, anxiety and stress among young people attending a private university in South-West Nigeria, revealed a prevalence of as high as 67.8% for anxiety (10). Another study, a multicentre study, done among university pharmacy students in different parts of Nigeria by Aluh et al (11) also revealed a high prevalence of anxiety (63.5%).…”
Section: Discussionmentioning
confidence: 88%